Uji Efektivitas Ekstrak Etanol Daun Bidara (Ziziphus spina- christi L.) terhadap Pertumbuhan Propionibacterium acne - Nurul Marfu’ah; Chelsea Aulia Ramadhani; Aural Miftahul Hasanah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Traditional medicinal plants can prove the importance of natural ingredients for various processes of human medicine. In recent years, there has been an increase in researchers' interest in the use of natural materials as natural biological compounds in the manufacture of drugs. One of the plants used as medicine by the community is bidara plants. Plant bidara contains phenolics and flavonoids which are rich in antibacterial properties. One of the bacteria that causes acne is Propionibacterium acnes. Untrated pimples will cause serious illness. Therefore, this study was conducted to determine the antibacterial activity of the ethanol extract of bidara against Propionibacterium acnes. This is an experimental study with 3 concentrations of bidara leaf extract namely concentrations of 70%, 80%, 90% and using negative controls (aquadest) and positive control (clindamisin). Extract of bidara leaves is done by maceration using 70% ethanol solution. While the antibacterial test uses the agar diffusion method using a well. Data obtained in the form of inhibitory zone measurements were analyzed using Analysis of variants (ANOVA). The results of this study indicate that the ethanol extract of Bidara leaves with a concentration of 70%, 80%, and 90% is not effective in inhibiting the growth of Propionibacterium acnes bacteria.